2019
DOI: 10.1111/cup.13549
|View full text |Cite
|
Sign up to set email alerts
|

Localized juvenile spongiotic gingival hyperplasia: A report of 27 cases

Abstract: Background: Localized juvenile spongiotic gingival hyperplasia (LJSGH) is a poorly understood but distinctive inflammatory hyperplasia occurring in children and young adults. Fewer than 100 cases have been reported since its initial description.Methods: During the period of 2015 to 2018, cases of LJSGH were identified, retrieved and their clinical and histopathological data reviewed.Results: There were 27 cases, with a median age of 13 years (range 7-72 years).Twenty-four of 27 patients were less than 20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
0
13
0
5
Order By: Relevance
“…LJSGH finnes på festet gingiva, men behøver ikke alltid å omfatte den marginale gingivalrand (1). Frekvensen er relativt lik for begge kjønn (7).…”
Section: Klinikkunclassified
See 1 more Smart Citation
“…LJSGH finnes på festet gingiva, men behøver ikke alltid å omfatte den marginale gingivalrand (1). Frekvensen er relativt lik for begge kjønn (7).…”
Section: Klinikkunclassified
“…Wang og Jordan fant 27 LJSGH-pasienter i årene 2015 til 2018 i sitt arkiv og her var 3 stykker over 60 år. Disse 27 pasientene representerte kun 0,1% av alle biopsiene (n= 27901) (7). Tilstanden synes derfor å vaere sjelden, men man kan ikke utelukke at hyperplasien ofte blir feildiagnostisert slik at antallet pasienter med LJSGH kan vaere høyere enn antatt (8).…”
Section: Klinikkunclassified
“…Currently, approximately 221 cases have been described in which it has been demonstrated that it is not a pathology totally of juvenile predilection because there are reports of cases of patients whose presentation was during the sixth decade of life, indeterminate male-female ratio, that is, without predilection for one or the other gender, likewise it has been located in multiple areas of the attached gingiva in both arches, it was evidenced that being exophytic, this entity should be called "hyperplasia" and there are reports of localized and generalized cases [4]. On the other hand, it is considered as the gingival counterpart of acute spongiotic dermatitis [5]. It is currently described as a patchy or raised lesion, with a papillary, granular, or smooth surface, bright red in color with a velvety appearance; patients do not report any symptoms and may bleed when brushing their teeth [6].…”
Section: Introductionmentioning
confidence: 99%
“…The etiopathogenesis is not fully clarified, but there are several mechanisms proposed as possible causes of the disease, among which are: viral infections such as HIV or HPV [7], high levels of estrogen or progesterone [8], allergic, bacterial, and fungal factors, external factors such as trauma or orthodontics [3] and local factors such as biofilm or mouth breathing [5]. There is a possibility that it is an entity of odontogenic origin, since it tends to be in the anterior sector of the maxilla [3], so there is a theory that due to the reduction of space when the primary teeth are exfoliated there is residual tissue of the junctional epithelium after the eruption of the permanent teeth [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation